Original paperOptimal single 3T MR imaging sequence for HDR brachytherapy of cervical cancer - Dempsey, Claire; Arm, Jameen; Best, Leah; Govindarajulu, Geetha; Capp, Anne; O’Brien, Peter (Journal of Contemporary Brachytherapy, 2014)
Purpose: The superior image quality of 3 tesla (3T) magnetic resonance (MR) imaging in cervical cancer offers the potential to use a single image set for brachytherapy. This study aimed to determine a suitable single sequence for contouring tumour and organs at risk, applicator reconstruction, and treatment planning. Material and methods : A 3T (Skyra, Siemens Healthcare AG, Germany) MR imaging system with an 18 channel body matrix coil generated HDR cervical cancer brachytherapy planning images on 20 cases using plastic-based treatment applicators. Seven different T2-weighted Turbo Spin Echo (TSE) sequences including both 3D and contiguous 2D scans based on sagittal, axial (transverse), and oblique planes were analysed. Each image set was assessed for total scanning time and usefulness in tumour localization via inter- and intra-observer analysis of high-risk clinical target volume (HR CTV) contouring. Applicator reconstruction in the treatment planning system was also considered. Results: The intra-observer difference in HR CTV volumes between 2D and 3D axial-based image sets was low with an average difference of 3.1% for each observer. 2D and 3D sagittal image sets had the highest intra- and inter observer differences (over 15%). A 2D axial ‘double oblique’ sequence was found to produce the best intra- (average difference of 0.6%) and inter-observer (mean SD of 9.2%) consistency and greatest conformity (average 0.80). Conclusions : There was little difference between 2D and 3D-based scanning sequences; however the increased scanning time of 3D sequences have potential to introduce greater patient motion artifacts. A contiguous 2D sequence based on an axial T2-weighted turbo-spin-echo (TSE) sequence orientated in all planes of the treatment applicator provided consistent tumour delineation whilst allowing applicator reconstruction and treatment planning.